APLIKASI TEORI BELAJAR SIBERNETIK DAN MEDIA ILUSTRASI VISUAL DALAM MENINGKATKAN KETERAMPILAN BERBAHASA INGGRIS - Sriwati, Sriwati (Jurnal Sosial Politik Unla, 2020)
This research is designed to improve process's quality and student's achievement and speaking learning using in application of cybernatic learning theory and visual illustration media. This research was conducted for two cycler in the ninth grade of SMP Negeri 1 Sukabumi City. The class consist of 23 boys and 22 girls. Many procedures in this research. Firstly, planning plan. Secondly, implementation, and thirdly, observation or reflection. From the first cycle to the end we use to get data was analyzed qualitatively. The result can be looked of that the application of cybernatic learning theory and visual illustration media can improve English speaking skill. According to the result have gotten can be conclution firsly. Cybernetic theory and visual illustration media can improve studen's skill for speaking English. Secondly, cybernatic learning theory and visual illustration media can be improve student's creative's or get more spirit for creative speaking. Based and the last result, the researcher proposes some suggestions. 1. An English teachers is suggested to use the apllication of cybernatic learning theory and visual illustration media for learning speaking. 2. An English teacher is suggested to create for interesting class to the student's like to stay in it and study better.